Das schwedische Danken als akzeptierende Bestätigung einer Bitte. Gezeigt anhand von Beispielen aus institutionellem Gespräch - Zborowski, Piotr (Folia Scandinavica Posnaniensia, 2007)
The act of thanking is one of the most distinct linguistic phenomenain Swedish. Thanking is very often reciprocated with thanking, especially in conversation closings. This is regarded as a part of the Swedish communication patterns. The ritual occures also in terminal sequences of phone calls to the Swedish Poison Information Centre, which are treated as institutional conversation. However, other interesting ways of the use of Swedish thanking can also be observed in the middle parts (so called insertion sequences) of these calls. Thanking functions there as the speaker’s acceptance of a special type of request formulated by the conversation partner.